2017
DOI: 10.1002/jcla.22297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of direct antifungal susceptibility testing methods of Candida spp. from positive blood culture bottles

Abstract: BMD is a reference method to evaluate the antifungal susceptibility, direct application of BMD might provide reliable results at least 24 hours earlier. Direct DD method may be a qualitative alternative. Direct susceptibility testing methods may be very useful to initiating the appropriate treatment on time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In this context, the thiosulfinates derived from Allium spp., such as allicin, have demonstrated broad antifungal activity in numerous in vitro studies against yeasts of the genus Candida [ 21 , 22 , 23 ]. In the present work, the MICs obtained for antifungals were similar to those obtained in previous research, both in our geographical area [ 24 , 25 ] and in more remote areas [ 19 , 26 , 27 , 28 , 29 ]. The lowest MICs were obtained for C. albicans and C. tropicalis ; the highest for C. glabrata and C. krusei , especially in the case of azoles, which indicates that Candida species remain susceptible to commonly used antifungals and do not represent a problem for the therapeutic approach.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, the thiosulfinates derived from Allium spp., such as allicin, have demonstrated broad antifungal activity in numerous in vitro studies against yeasts of the genus Candida [ 21 , 22 , 23 ]. In the present work, the MICs obtained for antifungals were similar to those obtained in previous research, both in our geographical area [ 24 , 25 ] and in more remote areas [ 19 , 26 , 27 , 28 , 29 ]. The lowest MICs were obtained for C. albicans and C. tropicalis ; the highest for C. glabrata and C. krusei , especially in the case of azoles, which indicates that Candida species remain susceptible to commonly used antifungals and do not represent a problem for the therapeutic approach.…”
Section: Discussionsupporting
confidence: 90%
“…To date, only three studies have directly evaluated DDT use for assessing fluconazole susceptibility in Candida species isolated from positive blood cultures [ 10 , 11 , 24 ]. These studies reported excellent CA between conventional (using colonies subcultured from positive blood cultures) and direct (using blood culture broth) DDT of fluconazole susceptibility [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disk diffusion testing (DDT), one of the oldest approaches to susceptibility testing, is still widely used in clinical laboratories because of its low cost and technical simplicity [ 8 ]. DDT has recently been used for the direct testing of bacterial or fungal susceptibility in positive blood cultures [ 9 11 ]. Methods for shortening the incubation times for DDT have recently been reported for several common bacterial pathogens, enabling faster reporting of antimicrobial susceptibility test results from positive blood cultures [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current methods for the rapid detection of resistance include molecular-based analyses [ 49 , 50 ], flow cytometry [ 51 ] or porous aluminum oxide (PAO)-based cultures [ 52 , 53 ], which deliver results within a few hours. Furthermore, the improvement of the conventional methods by the direct inoculation of standard tests with positive blood cultures [ 54 ] or shortening the time to result by automated approaches such as as the Vitek 2 yeast panel [ 55 , 56 , 57 ] have been investigated. However, all of these methods have their own limitations of applicability, diagnostic accuracy or time to result.…”
Section: Discussionmentioning
confidence: 99%